2010
DOI: 10.1089/dia.2009.0129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Meglitinides on Postprandial Ghrelin Secretion Pattern in Type 2 Diabetes Mellitus

Abstract: Treatment with meglitinides reconstructed postprandial ghrelin secretion patterns to those of controls without diabetes. This observation may help to improve the control of feeding behavior in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Moreover, a recent study found that treatment with repaglinide and nateglinide reconstructed postprandial ghrelin secretion patterns in diabetes, and thus nateglinide may help to improve the control of feeding behavior in patients with T2DM. 28 A few limitations to our study design should be considered when interpreting our results. In particular, the study population was relatively small, and the observation time was…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a recent study found that treatment with repaglinide and nateglinide reconstructed postprandial ghrelin secretion patterns in diabetes, and thus nateglinide may help to improve the control of feeding behavior in patients with T2DM. 28 A few limitations to our study design should be considered when interpreting our results. In particular, the study population was relatively small, and the observation time was…”
Section: Discussionmentioning
confidence: 97%
“…The mealinduced decrease of ghrelin levels is impaired in type 2 diabetic subjects [20], suggesting that the impaired suppression of circulating ghrelin during the meal intake may partly account for the glucose intolerance as well as ongoing weight gain in type 2 diabetes. When wild-type and ghrelin-KO mice were fed a high-fat diet (HFD), both mouse lines developed moderate increases in body weight to a similar extent [8].…”
Section: Ghrelin As a Potential Therapeutic Target For Type 2 Diabetesmentioning
confidence: 99%